The Contribution of E-Learning Platforms to Enhance Students’ English Skills in Learning ESP - Faiz Rizaldi; Ni Luh Putu Era Adnyayanti (Pusat Studi Bahasa dan Publikasi Ilmiah, 2021)
In a pandemic situation, the students and teachers should adapt a new educational system required to implement online learning. The research aims to investigate the contribution of online platforms in enhancing students in learning of ESP. The study was conducted in SMK Nusa Dua Gerokgak. The study involved the students of SMK Nusa Dua Gerokgak. The observation and interview were done to collect the data. The results revealed that some online platforms use to help them in learning ESP. However, WhatsApp is the most frequent platform used since it is easier to use, and students are familiar with it.